New N(4)-methylthiosemicarbazone derivatives: Synthesis, characterization, structural properties, DNA interactions and antiproliferative activity - Hussein, Mouayed; Guan, Teoh Siang (European Journal of Chemistry, 2015)
Five new thiosemicarbazone compounds derived from N(4)-methylthiosemicarbazide and 5-bromo-2-hydroxybenzaldehyde (1), 2,4-dihydroxybenzaldehyde (2), 3-ethoxy-2-hydroxy benzaldehyde (3), 3-tert-butyl-2-hydroxybenzaldehyde (4), and 2-acetylpyridine (5) have been synthesized. The molecular structures of the prepared compounds were identified using by single crystal X-ray crystallography. The binding properties of the compounds with calf thymus DNA were analyzed by UV, fluorescence titration, and viscosity measurements. The cytotoxic properties of the compounds were tested against human colorectal cell lines (HCT 116). The compounds showed greater pronounced activity than the standard reference drug 5-fluorouracil (IC50 = 7.3 μM). The results showed that the activity strength of these compounds depends on the lipophilic properties that provided by the terminal N(4)-substituent and aromatic ring-substituent, as well as the planarity that provided by the geometrical and conformational structures of the compounds.